2010
DOI: 10.1111/j.1556-4029.2010.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characterization of Some Modern “Eco‐Friendly” Fibers*

Abstract: Fibers that are termed "eco-friendly" or "biodegradable" by manufacturers are increasingly being used in textile products such as apparel and carpeting to appeal to the ever more environmentally aware public. As such, these modern fibers are expected to begin showing up more often in forensic casework, and it is important that the forensic examiner recognize them. This study employed polarized light microscopy (PLM) and Fourier transform infrared (FTIR) microspectroscopy to characterize selected fibers of azlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…0.03. These values are consistent with the modern generation of azlons compared to the azlons produced prior to the 1950s, which had much lower birefringence values of 0–0.006 . The modern fibers tested exhibited parallel extinction with some partial (undulose) extinction, and a positive sign of elongation.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…0.03. These values are consistent with the modern generation of azlons compared to the azlons produced prior to the 1950s, which had much lower birefringence values of 0–0.006 . The modern fibers tested exhibited parallel extinction with some partial (undulose) extinction, and a positive sign of elongation.…”
Section: Resultssupporting
confidence: 81%
“…Currently, new production methods, including incorporating polyvinyl alcohol into the spinning solution , have resulted in modern azlons. These azlons have different optical properties than their predecessors . Textiles may be 100% azlon or blended with cotton, silk, nylon, or wool.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The absorption bands at 1636−1680, 1533−1559, and 1241−1472 cm −1 were ascribed to the amide I, amide II, and N−H bending (amide III) vibrations in peptide bonds forming the primary backbone of soy proteins. 13,14 This result indicated that the SP and PVA in the polar solvent (formic acid) had a good compatibility for homogeneous blending.…”
Section: Resultsmentioning
confidence: 84%
“…The morphological structure of SPF consists of less oriented sheath and well oriented microfibrilar core. The fibres have about 10% of hydrophilic groups in amorphous regions (Mathur & Hira, 2004 (Brinsko, K. M., 2010).…”
Section: Pure Soybean Protein Fibres From the Mid-twentieth Centurymentioning
confidence: 99%